Hierarchical Cascade Controller for Assistance Modulation in a Soft Wearable Arm Exoskeleton - Binh Khanh Dinh; Xiloyannis, Michele; Antuvan, Chris Wilson; Cappello, Leonardo; Masia, Lorenzo (IEEE robotics and automation letters, 2017)
In recent years soft wearable exoskeletons, commonly referred to as exosuits, have been widely exploited in human assistance. Hence, a shared approach for a systematic and exhaustive control architecture is extremely important. Most of the exosuits developed so far employ a bowden cable transmission to conveniently place the actuator away from the end-effector. While having many advantages this actuation strategy presents some intrinsic limitations caused by the presence of nonlinearities, such as friction and backlash of the cables, which make it difficult to predict and control the dynamics between the device and the user. In this letter, we propose a novel hierarchical control paradigm for a cable-driven upper limb exosuits that aims at evaluating and consequently deliver the appropriate assistive torque to the user's elbow joint. The proposed control method comprises three main layers: an active impedance control which estimates the user's arm motion intention and guarantees an intuitive response of the suit to the wearer's motion; a mid-level controller which compensates for the backlash in the transmission and converts the reference arm motion to the desired position of the actuator; a low-level controller which is responsible for driving the actuation stage by compensating for the nonlinear dynamics occurring in the bowden cable to provide the desired assistive torque at the joint. Tests on healthy subjects show that wearing the exosuit reduces by 48.3% the muscular effort required to lift 1 kg and that the controller is able to modulate its level of assistance to the wearer's motor ability.